2017
DOI: 10.1007/s11631-017-0163-5
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical tracing and modeling of surface and deep water–rock interactions in elementary granitic watersheds (Strengbach and Ringelbach CZOs, France)

Abstract: From the study of the Strengbach and Ringelbach watersheds we propose to illustrate the interest of combining the geochemical tracing and geochemical modeling approaches on surface and deep borehole waters, to decipher the diversity of the water flow and the associated water-rock interactions in such elementary mountainous catchments. The results point to a clear geochemical typology of waters depending on the water circulations (deep vs. hypodermic) within the substratum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 14 publications
3
17
0
Order By: Relevance
“…Therefore, aquifer groundwater age increases with depth (Armandine Les Landes et al 2015;Roques et al 2014a), and mineral content increases by water-rock interactions, and with the part of the weathering profile in which the groundwater is flowing (e.g. Chabaux et al 2017;Babaye et al 2019). Consequently, the composite aquifer may show a strong vertical hydrogeochemical stratification, both in the saprolite (Durand et al 2006;de Montety et al 2018) and in the SFL (Alazard et al 2016)-for example, in some watersheds, there is an increase of fluoride concentration with depth (Pauwels et al 2015), and an increase of ages with depth, even in the saprolite (de Montety et al 2018).…”
Section: Hydrogeological Functioning Of Hr Aquifers: Hydrochemistrymentioning
confidence: 99%
“…Therefore, aquifer groundwater age increases with depth (Armandine Les Landes et al 2015;Roques et al 2014a), and mineral content increases by water-rock interactions, and with the part of the weathering profile in which the groundwater is flowing (e.g. Chabaux et al 2017;Babaye et al 2019). Consequently, the composite aquifer may show a strong vertical hydrogeochemical stratification, both in the saprolite (Durand et al 2006;de Montety et al 2018) and in the SFL (Alazard et al 2016)-for example, in some watersheds, there is an increase of fluoride concentration with depth (Pauwels et al 2015), and an increase of ages with depth, even in the saprolite (de Montety et al 2018).…”
Section: Hydrogeological Functioning Of Hr Aquifers: Hydrochemistrymentioning
confidence: 99%
“…By construction, NIHM can only model shallow water dynamics (section Water cycle monitoring), so that deeper water circulation pathways in the granitic bedrock fractures (as evidenced in deep boreholes, Ranchoux et al, 2021) is not taken into account with this modeling approach, which makes hypothesis (i) plausible. However, the analysis of the geochemical signatures of the spring water and the water collected from observation wells (>50 m deep boreholes and <15 m deep piezometer) showed that the springs water and the piezometers water circulate within the same surface aquifer with a low water residence time, while the water from the deep boreholes circulates in a distinct circulation system, within the fracture network of the granitic bedrock, and is characterized by much higher residence times (Chabaux et al, 2017;Ranchoux et al, 2021). So that when modeling water dynamics inside the Strengbach catchment, neglecting deep water circulation-as it is done by NIHM-is a reasonable hypothesis.…”
Section: Limits Of the Approachmentioning
confidence: 99%
“…It was selected in 1986 to study and understand the impact of acid rain on the forested ecosystem (Probst et al, 1990;Pierret et al, 2019). Then, it was progressively and extensively used to understand the main hydrobiogeochemical processes occurring in this type of ecosystem, using a large diversity of geochemical tracing and geochronological approaches (Pierret et al, 2014;Schmitt et al, 2017 andPrunier et al, 2015;Chabaux et al, 2017 and and, more recently, hydrogeochemical modeling (Beaulieu et al, 2016;Weill et al, 2017;Maquin et al, 2017;Belfort et al, 2018;Ackerer et al, 2018;Weill et al, 2019).…”
Section: Site Descriptionmentioning
confidence: 99%